Understanding Tax Avoidance on Bank Debts Reviewed from the Letter An Nisa 29 - Alan Januar Ahmed; Leniwati, Driana; Juanda, Ahmad (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Purpose: This study aims to analyze tax avoidance on bank debts reviewed from the letter An Nisa 29 by paying attention to Islamic business ethics and the perspective of the letter An-Nisa verse 29. Method: This study uses a qualitative approach with the type of library research. The data collection techniques used in this study are non-participant observation, interviews, and libraries. Data are analyzed using data reduction, data presentation, and drawing conclusions. Results: The main principles in Islamic business ethics that are contrary to tax avoidance include the principle of honesty, the principle of awareness of social significance in business activities, the principle of justice, the principle of good intentions, and the principle of trust. Thus it is clear that tax avoidance which is part of a vicious circle is prohibited in Islam. Based on Surah An-Nisa verse 29 there are four main points of discussion that can be developed to see tax avoidance activities on bank debt. The four points are wealth, false path, mutual consent, and do not kill yourselves. Implications: This research provides implications for accounting science, especially regarding the analysis of tax avoidance on bank debt as reviewed from the letter An Nisa 29. Novelty: This study focuses on the analysis of tax avoidance on bank debt reviewed from the letter An Nisa 29 with indicators of Islamic business ethics, namely the principle of honesty, the principle of awareness of social significance in business activities, the principle of justice, the principle of good intentions, and the principle of trust. Then integrated into the review of the letter An-Nisa verse 29 there are four main points of discussion, namely wealth, the wrong path, mutual consent, and do not kill yourselves.